Listening beyond the border: Self-representation, witnessing, and the white sonic field - Andrew Brooks (Law Text Culture, 2020)
This paper considers the relationship between sound and the structural violence of whiteness in the context of the Australian settler colony. It thinks with an archive of audio recordings made by the Manus Recording Project Collective, a group of men currently or formerly held in involuntary and indefinite detention after seeking asylum in Australia, and their collaborators in Melbourne. Tracking the demonisation of refugees in the media and party politics over the past two decades, I develop the notion of the white sonic field as a way of accounting for the way both sound and perception are racially saturated in the settler colony. The sonic field, which comprises both the sounds we hear and the forces that mediate our hearing, is crucial to the maintenance of whiteness in the settler state, structuring perception and naturalising settlement through the repetition of possessive speech acts and the selective silencing of non-white voices. Cutting through the white sonic field are recordings from the where are you today archive produced by the Manus Recording Project Collective. I argue that these recordings reclaim the right to representation, moving beyond both the erasure of refugees and spectacle of their suffering. These recordings compel us to listen beyond the border and beyond the white sonic field, asking us to consider how we might dismantle the carceral system of mandatory and indefinite detention.